14-4(x-3)=2(2x+8)-5

Simple and best practice solution for 14-4(x-3)=2(2x+8)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-4(x-3)=2(2x+8)-5 equation:



14-4(x-3)=2(2x+8)-5
We move all terms to the left:
14-4(x-3)-(2(2x+8)-5)=0
We multiply parentheses
-4x-(2(2x+8)-5)+12+14=0
We calculate terms in parentheses: -(2(2x+8)-5), so:
2(2x+8)-5
We multiply parentheses
4x+16-5
We add all the numbers together, and all the variables
4x+11
Back to the equation:
-(4x+11)
We add all the numbers together, and all the variables
-4x-(4x+11)+26=0
We get rid of parentheses
-4x-4x-11+26=0
We add all the numbers together, and all the variables
-8x+15=0
We move all terms containing x to the left, all other terms to the right
-8x=-15
x=-15/-8
x=1+7/8

See similar equations:

| 0=m/9+1 | | x/2-3x-3/2=x/2+9/2+4 | | -3+3x=54 | | 2n^=64 | | 2+3(x-2)=3x-4 | | 17+2x=157 | | 5,6x-7,3=2,2+1,8x | | 14=3n+99 | | 9q=7q-2 | | -5=-6v+7+2v | | 9b+10=7b-10 | | 14=-7k-7k | | 3.8x(-1-1.9x)=2.6+13.3x | | w/4+5=13 | | -2r=-10-r | | 10(v+4)=60 | | 15d+6(-5d+9)=16+8d−8 | | -2r=-10−r | | 10z−13=27 | | 25=z/9+22 | | -5+2y-9+y=25 | | -12x+5=3x-10-15x | | 21.75-47/4=v | | m4=40 | | 4z=7+5z | | 2(1.5-x)+42=103-4(3x+7) | | -25=5/4r | | v-47/4=10 | | -17w=187 | | p-89/3=3 | | w-14=19 | | 8=8p+13=3p |

Equations solver categories